Cloning, expression and optimized production in a bioreactor of bovine chymosin B in Pichia (Komagataella) pastoris under AOX1 promoter - Noseda, Diego Gabriel (2013)
The codon sequence optimized bovine prochymosin B gene was cloned under the control of the alcohol oxidase 1 promoter (AOX1) in the vector pPIC9K and integrated into the genome of the methylotrophic yeast Pichia (Komagataella) pastoris (P. pastoris) strain GS115. A transformant clone that showed resistance to over 4 mg G418/ml and displayed the highest milk-clotting activity was selected. Cell growth and recombinant bovine chymosin production were optimized in flask cultures during methanol induction phase achieving the highest coagulant activity with low pH values, a temperature of 25 °C and with the addition of sorbitol and ascorbic acid at the beginning of this period. The scaling up of the fermentation process to lab-scale stirred bioreactor using optimized conditions, allowed to reach 240 g DCW/L of biomass level and 96 IMCU/ml of milk-clotting activity. The enzyme activity corresponded to 53 mg/L of recombinant bovine chymosin production after 120 h of methanol induction. Western blot analysis of the culture supernatant showed that recombinant chymosin did not suffer degradation during the protein production phase. By a procedure that included high performance gel filtration chromatography and 3 kDa fast ultrafiltration, the recombinant bovine chymosin was purified and concentrated from fermentation cultures, generating a specific activity of 800 IMCU/Total Abs280 nm and a total activity recovery of 56%. This study indicated that P. pastoris is a suitable expression system for bioreactor based fed-batch fermentation process for the efficient production of recombinant bovine chymosin under methanol-inducible AOX1 promoter.